Electronic notification in the European Judicial Area. Challenges and issues - Marchal Escalona, Nuria (CUADERNOS DE DERECHO TRANSNACIONAL, 2023)
Technological tools contribute to improving access to justice, to the elimination of geographical and time barriers, as well as to the reduction of procedural costs. This explains why the European legislator has recently focused its efforts on promoting and implementing the digitisation of service in cross-border judicial proceedings. The aim of this study is to contribute to the reflection on the challenges that the digitisation of service poses in the European judicial area. To this end, we will analyse to what extent the new European law responds to the needs that electronic notification poses and, most importantly, whether or not it complies with the most basic requirements of justice. We will also look at the question of language in cross-border electronic notification. To this end, we will analyse and assess the position adopted by the Court of Justice of the European Union in this area.
Keywords: European judicial area; Regulation (EU) 2020/1784; decentralised system; direct electronic notification; Proposal for a Digitisation Regulation; right to legal protection; language issues